Pengaruh Kemudahan Akses Terhadap Loyalitas Nasabah Pengguna Aplikasi Byond By BSI Dengan Kepuasan Nasabah Sebagai Variabel Mediasi (Studi Kasus Bank Syariah Indonesia KCP Padang UPI YPTK) - Rifa Ramadhani; Yofina Mulyati (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of ease of access on customer loyalty among users of the Byond by BSI application, with customer satisfaction as a mediating variable at Bank Syariah Indonesia KCP Padang UPI YPTK. The population of this study consists of all customers who use the Byond by BSI application at BSI KCP Padang UPI YPTK, with a sample size of 100 respondents. The sampling technique in this study user purposive sampling technique, This research employs a quantitative method using the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. The results indicate that Ease of access has a positive but insignificant effect on customer loyalty; Ease of access has a positive and significant effect on customer satisfaction; Customer satisfaction has a positive and significant effect on customer loyalty; and Ease of access has a positive and significant effect on customer loyalty mediated by customer satisfaction.